Effects of l-tyrosine amino acid on competitive performance of 17-19 years old academic table tennis players - Romanov, Y. N.; Romanova, L. A.; Knyazev, S. A.; Lyapina, A. L. (Theory and Practice of Physical Culture, 2019)
Objective of the study was to analyze benefits of aromatic amino acid L-tyrosine administration for competitive performance and psychophysiology test rates of the 17-19 year old academic table tennis players. Sampled for the study were the South Ural State University students (n=20) aged 18.83±0.10 years, weighing 69.75±1.90 kg and 180.20±1.72 cm tall, trained twice a week under the academic Physical Education and Sport curricula and split up into two groups (EG and RG) of 10 people each. Competitive performance of the sample was tested in a daily table tennis Olympics-modeling tournament. One hour prior to the tournament the EG administered L-tyrosine pills (5g, made by Twinlab, USA); and the RG took placebo of microcrystal cellulose (5g, made by Evalar, Russia); with both agents taken with 400ml of fresh orange juice. Prior and 1 hour after administration of the agents the sample was tested to obtain the WAM, attention focusing, short-term memorizing and thinking abilities and nervous reactivity test rates. Both of the groups competed in the academic table tennis tournament 1 hour after administration of the agents. The tests found a significant growth of the WAM (p<0.05) and short-term memorizing ability (p<0.01) in the EG upon administration of L-tyrosine; that could be one of the reasons for the EG win in the tournament. The test data and competitive success may be interpreted as indicative of the L-tyrosine administration being beneficial for the competitive performance.